Pelatihan Mendeley, Tracing Journal dan Penulisan Sitasi di Journal - Sitanggang, Eva Rianty; Syamsuddin, Syamsuddin; Nurmalini, Nurmalini (Jurnal Mitra Pengabdian Farmasi, 2023)
In carrying out Tridharma activities in higher education, all students and lecturers in tertiary institutions need to understand the principles of good and scientific research so that the results of their writing can be of high quality. However, many writers experience difficulties in conducting research where one of the questions is the accuracy of the author in seeing the errors in the writing produced to be published on social media in the context of spreading knowledge. One of the tools used to see author errors is the Mendeley Application which assists researchers in producing good and scientific writing. Then the results of scientific work must be supported by references from various reading sources that strengthen the value of our research results which are called citations. Overall, the results of scientific work produced by students and lecturers must go through various scientific stages so that they have good value which is disseminated through national and international journals.